INCLUSION POLICY OF CIUDAD DEL ESTE COMPANIES FOR THE HIRING OF PEOPLE WITH DISABILITIES - Prieto Gayoso , Anastacia; Carolina Oviedo Mora, Leidi; Rocío Santander Barreto, Raquel (Revista Gênero e Interdisciplinaridade, 2023)
The present study is oriented towards the Inclusion Policy of the Companies of Ciudad del Este for the Hiring of Persons with Different Capacities implemented within some public or private companies of Ciudad del Este. For this, an investigation was carried out with a mixed approach, where it was designed a structured survey that has been applied to officials with different capacities of some public and private companies in Ciudad del Este and an interview carried out in the exclusive department to those in charge of people with said capacity. The results of the field work made it possible to show that the strategies applied during the process of this work responded effectively in terms of the inclusion laws that show the incorporation of people with different abilities within the Public entity and the same as not comply with the provisions will be sanctioned with an established fine.